1995
DOI: 10.1108/01443579510090318
|View full text |Cite
|
Sign up to set email alerts
|

A review of the order release policy research

Abstract: Reviews a critical aspect of job shop scheduling research, namely the decision regarding release timing of orders to the manufacturing shopfloor. Covers articles specifically addressing the order release problem; the information should prove helpful for researchers employing order release policies in their research. The release decision literature is classified into three areas: descriptive studies including case and survey research, analytical or optimization‐based research, and simulations of theoretical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 33 publications
0
39
0
2
Order By: Relevance
“…This stage has received far more attention in the literature than the preceding stages (e.g. Wisner, 1995;Bergamaschi et al, 1997). Breithaupt et al (2002) reported that the order release mechanism of load-oriented manufacturing control (see Bechte, 1988) was previously included in the SAP R/2 system and the systems of some domestic ERP vendors in Germany.…”
Section: Mto Requirements and Erp Functionality At The Order Release mentioning
confidence: 99%
“…This stage has received far more attention in the literature than the preceding stages (e.g. Wisner, 1995;Bergamaschi et al, 1997). Breithaupt et al (2002) reported that the order release mechanism of load-oriented manufacturing control (see Bechte, 1988) was previously included in the SAP R/2 system and the systems of some domestic ERP vendors in Germany.…”
Section: Mto Requirements and Erp Functionality At The Order Release mentioning
confidence: 99%
“…The WLC concept presented in the literature differs in the account of workload overtime, release mechanisms, workload norms, and levels of PPC decisions (see Land and Gaalman 1996;, whereas the commonality is the use of a pre-shop pool/buffer to regulate shop-floor congestion and reduce work-inprogress (Wisner 1995). This paper mainly considers an aggregate load-oriented approach -originating from the doctoral work of Tatsiopoulos (1983) and at the Lancaster University Management School (hereafter referred to as the LUMS approach) -in determining WLC data requirements due to its comprehensive coverage of the PPC decisions and effectiveness in improving shop-floor performance in practice (see Stevenson and Hendry 2006;.…”
Section: "What Information Is Required To Support Successful Implemenmentioning
confidence: 99%
“…Other studies have attempted to provide an overview of WLC research but have tended to focus on describing the various ORR mechanisms (e.g. Melnyk and Ragatz 1988, Wisner 1995, Bergamaschi et al 1997 or comparing them through simulation (e.g. Philipoom et al 1993, Sabuncuoglu andKarapinar 1999) and hence do not incorporate all PPC stages within the scope of WLC.…”
Section: Introductionmentioning
confidence: 98%